Coordination Tunes Selectivity: Two‐Electron Oxygen Reduction on High‐Loading Molybdenum Single‐Atom Catalysts - Tang, Cheng; Jiao, Yan; Shi, Bingyang; Liu, Jia‐Ning; Xie, Zhenhua; Chen, Xiao; Zhang, Qiang; Qiao, Shi‐Zhang (Angewandte Chemie (International ed.), 2020)
Single‐atom catalysts (SACs) have great potential in electrocatalysis. Their performance can be rationally optimized by tailoring the metal atoms, adjacent coordinative dopants, and metal loading. However, doing so is still a great challenge because of the limited synthesis approach and insufficient understanding of the structure–property relationships. Herein, we report a new kind of Mo SAC with a unique O,S coordination and a high metal loading over 10 wt %. The isolation and local environment was identified by high‐angle annular dark‐field scanning transmission electron microscopy and extended X‐ray absorption fine structure. The SACs catalyze the oxygen reduction reaction (ORR) via a 2 e− pathway with a high H2O2 selectivity of over 95 % in 0.10 m KOH. The critical role of the Mo single atoms and the coordination structure was revealed by both electrochemical tests and theoretical calculations. The cat in the SAC: Mo single‐atom catalysts (SACs) with a unique O,S coordination exhibit outstanding H2O2 selectivity above 95 % in the oxygen reduction reaction (ORR). Electrochemical tests and theoretical calculations revealed the critical role of the coordination structure in SACs, highlighting new opportunities to tune the activity and selectivity in multi‐electron electrocatalysis.